Journal of Experimental Neurology 2021
DOI: 10.33696/neurol.2.044
|View full text |Cite
|
Sign up to set email alerts
|

Differential Fecal Microbiome Dysbiosis after Equivalent Traumatic Brain Injury in Aged Versus Young Adult Mice

Abstract: TBI symptoms in young patients is well documented in the literature demonstrating patterns of impairment in communication, behavior, higher-order cognition, and learning efficiency [10][11][12].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 57 publications
1
5
0
Order By: Relevance
“…Moreover, reduced evenness and abundance of gut microbiota were reflected in Shannon, Simpson, and Fisher indices in both male and female mice. These alpha diversity-related changes in gut microbiota following CCI correspond with the earlier research findings ( Nicholson et al, 2019 ; Davis et al, 2021 , 2022 ; Du et al, 2021 ; Frankot et al, 2023 ). The bidirectional crosstalk of the brain and gut microbiota has also been evident in the management of brain injuries such as stroke, spinal cord injuries, and TBI ( Singh et al, 2016 ; Akhoundzadeh et al, 2018 ; Sun et al, 2018 ; Ma et al, 2019 ; Devi et al, 2021 ; Frankot et al, 2023 ).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Moreover, reduced evenness and abundance of gut microbiota were reflected in Shannon, Simpson, and Fisher indices in both male and female mice. These alpha diversity-related changes in gut microbiota following CCI correspond with the earlier research findings ( Nicholson et al, 2019 ; Davis et al, 2021 , 2022 ; Du et al, 2021 ; Frankot et al, 2023 ). The bidirectional crosstalk of the brain and gut microbiota has also been evident in the management of brain injuries such as stroke, spinal cord injuries, and TBI ( Singh et al, 2016 ; Akhoundzadeh et al, 2018 ; Sun et al, 2018 ; Ma et al, 2019 ; Devi et al, 2021 ; Frankot et al, 2023 ).…”
Section: Discussionsupporting
confidence: 90%
“…We also noted the increased abundance of P. copri in the CCI_M → F group. In this way, sex-specific characterization of gut microbiota phenotypes may be useful for predicting post-TBI neurological recovery and crafting better therapeutic approaches ( Luczynski et al, 2016 ; Sundman et al, 2017 ; Davis et al, 2021 ; Du et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Age, in the setting of TBI, has also been shown to affect dysbiosis as well. One study showed that older mice subjected to TBI had greater changes in disease-associated microbial species compared to younger mice counterparts [ 36 ]. Another group performed repetitive TBI on adolescent and adult male and female rats, showing that while there were no differences between age groups in terms of diversity or taxonomy at 17 or 30 days postinjury, pre-injury depletion of the microbiome resulted in a postinjury microbiome with a pathogenic proinflammatory profile, with decreases in commensal bacteria such as Bacteroides and Bifidobacterium , which was worse in adolescents [ 37 ].…”
Section: Traumamentioning
confidence: 99%
“…Notably, older mice subjected to TBI displayed different gut flora environments than younger mice. 154 Indeed, the microbiome may undergo a spectrum of changes over time following TBI, making analysis of gut flora a possible venue for injury prognostication. 155 However, TBI-induced changes in the gut microbiome may be alleviated through faecal transplant which, again, has been demonstrated to improve cognitive performance in mice.…”
Section: Traumatic Brain Injurymentioning
confidence: 99%